Treatment outcomes of bladder stones in children with intact bladders in developing countries: A systematic review of >1000 cases on behalf of the European Association of Urology Bladder Stones Guideline panel. Issue 2 (April 2022) - Davis, N.F.; Donaldson, J.F.; Shepherd, R.; Neisius, A.; Petrik, A.; Seitz, C.; Thomas, K.; Lombardo, R.; Tzelves, L.; Somani, B.; Gambarro, G.; Ruhayel, Y.; et al.
Summary: Introduction: Bladder stones (BS) are still endemic in children in developing nations and account for a high volume of paediatric urology workload in these areas. The aim of this systematic review is to comparatively assess the benefits and risks of minimally invasive and open surgical interventions for the treatment of bladder stones in children. Methods: This systematic review was conducted in accordance with Cochrane Guidance. Database searches (January 1970– March 2021) were screened, abstracted, and assessed for risk of bias for comparative randomised controlled trials (RCTs) and non-randomised studies (NRSs) with >10 patients per group. Open cystolithotomy (CL), transurethral cystolithotripsy (TUCL), percutaneous cystolithotripsy (PCCL), extracorporeal shock wave lithotripsy (ESWL) and laparoscopic cystolithotomy (LapCL) were evaluated. Results: In total, 3040 abstracts were screened, and 8 studies were included. There were 7 retrospective non-randomised studies (NRS's) and 1 quasi-RCT with 1034 eligible patients (CL: n=637, TUCL: n=196, PCCL: n=138, ESWL: n=63, LapCL n=0). Stone free rate (SFR) was given in 7 studies and measured 100%, 86.6%-100%, and 100% for CL, TUCL and PCCL respectively. CL was associated with a longer duration of inpatient stay than PCCL and TUCL (p<0.05). One NRS showed that SFR was significantly lower after 1 session with outpatient ESWL (47.6%) compared to TUCL (93.5%) and CL (100%) (p<0.01 and p<0.01 respectively). One RCT compared TUCL with laser versus TUCL with pneumatic lithotripsy and found that procedure duration was shorter with laser for stones <1.5cm (n=25, p=0.04). Conclusion: In conclusion, CL, TUCL and PCCL have comparable SFRs but ESWL is less effective for treating stones in paediatric patients. CL has the longest duration of inpatient stay. Information gathered from this systematic review will enable paediatric urologists to comparatively assess the risks and benefits of all urological modalities when considering surgical intervention for bladder stones.